Molecular Detection and Treatment of Trypanosomiosis in a Cat: A Case Report - Jafarsab; Mamatha, Gotakanapura Sanjeevamurthy; Kumar, Niteesh; Bijurkar, Rajeshwar Gangaram; Doddamane, Rathnamma (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
Trypanosomosis is one of the most common and  important haemoprotozoan disease that affects humans  and animals including cats (Mohammed et al., 2022). The  aetiological agent for trypanosomiosis in cats is T. evansi  and T. brucei (Priyowidodo et al., 2023). The disease has  wide distribution in Africa, Asia, and Latin America (Da  Silva et al., 2010) and mainly transmitted mechanically by  biting flies such as Tabanus, Stomoxys and triatomids bugs  or by feeding on infected meat (Sivajothi and Sudhakara  Reddy, 2017; Mohammed et al., 2022). Infected cats show  clinical signs such as anorexia, diarrhoea, decrease in  weight, progressive anaemia, lethargy, lymphadenopathy,  hyperthermia, corneal opacity, edema around the eyes and  in-coordination (Da Silva et al., 2011: Sivajothi and Sudhakara  Reddy, 2017: Priyowidodo et al., 2023). The rapid diagnosis  of trypanosomosis in animals is commonly attempted  by examination of wet mount smears, and blood smears  stained with Romanowsky stains such as Giemsa stain.  The polymerase chain reaction (PCR) technique can be  performed for further confirmatory diagnosis (Mohammed  et al., 2022: Priyowidodo et al., 2023). However, there  was a paucity of literature available on natural infection  of feline trypanosomosis in the world (Sivajothi and  Sudhakara Reddy, 2017), Hence, the present case study on  trypanosomosis in cat and its successful treatment in Bidar  district, Karnataka, India is reported.
Keywords: progressive anaemia; Romanowsky stains; trypanosomosis; Giemsa stain